A Close Reading on Henri Lefebvre’s Urban Form and Criticism - Ng, Keng Khoon (MAJ - Malaysia Architectural Journal, 2020)
This paper intends to perform a close reading and skeptical reflection on Henri Lefebvre’s ideas of ‘urban form’ by referencing to the book – The Urban Revolution (1970; English translation published in 2003). Lefebvre’s major urbanism debate – The Urban Revolution was published in the 1970. Despite nearly half a century this book was pulished, it continues to serve as a foundational literature for coming generations of urban thinkers or scholars. This paper is not a book review of Lefebvre’s The Urban Revolution, but the intention of this paper is to appraise closely on the selected theme of ‘urban from’ as discussed in this book. The proposition in performing this close reading is principally to ask: how have the architectural designs and planning regimes of urbanism become an urban practice of ideology, utopia and power? The paper suggests a new framework of interpretation which could be useful for architects and architectural students to comprehend or reflect on this highly dialectic concept of urban form.